Relationship of stiffness and damping ratio with strain for residual soils - Yeo, Sir Hoon (2008)
There is very little work done on characterization of soil stiffness and damping ratio with strain for residual soils in Singapore. This is because routine geotechnical design does not usually incorporate the non-linearity of soil stiffness and damping ratio is only needed for dynamic problems. However, the use of large strain (>1%) soil stiffness to compute ground movement is over conservative as the mobilized strain due to construction loads and working loads is usually in the range of 0.01% to 1%. Furthermore, the demand for seismic analysis is increasing due to ground tremors felt in Singapore arising from earthquakes in Indonesia.